2009
DOI: 10.1016/j.bmcl.2008.11.029
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazole derivatives as new cannabinoid CB1 receptor antagonists

Abstract: This letter reports the new entry of novel 1,2,3-triazole derivatives as CB1 receptor antagonists. The design, synthesis and biological evaluation of N1 and N2 substituted 1,2,3-trizoles are described. The N2 substituted, symmetrical 1,2,3-triazoles are more potent ligands than the unsymmetrical analogues. The in vitro activity of these triazoles is further improved by inserting a methylene group between the central core and the carbonyl side chain. The most potent antagonists prepared in this series (IC(50)<2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…[35][36][37] To synthesize the 4,5-disubstituted and the 1,4,5-and 2,4,5trisubstituted triazole units (Scheme 4), 4,4'-dicyanostilbene (22) was prepared as an intermediate for both series of compounds using Sonogashira reaction conditions between the 4bromobenzonitrile (21) and the 4-ethynylbenzonitrile (3) in the presence of palladium(II), copper(I) iodide and triethylamine. [47] The 1,4,5-trisubstituted triazole derivatives 25 a and 25 b were prepared using the copper(II)-catalyzed 1,3-dipolar cyclo- addition of azidobenzene 23 a or azidomethylbenzene 23 b to 4,4'-dicyanostilbene (22) at 65 8C, but the reaction did not work at this temperature probably due to steric hindrance; therefore, the temperature was increased to 120 8C. [32][33][34] The Pinner reaction was employed to obtain compounds 25 a and 25 b in yields of 22 % and 39 %, respectively, over two steps (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37] To synthesize the 4,5-disubstituted and the 1,4,5-and 2,4,5trisubstituted triazole units (Scheme 4), 4,4'-dicyanostilbene (22) was prepared as an intermediate for both series of compounds using Sonogashira reaction conditions between the 4bromobenzonitrile (21) and the 4-ethynylbenzonitrile (3) in the presence of palladium(II), copper(I) iodide and triethylamine. [47] The 1,4,5-trisubstituted triazole derivatives 25 a and 25 b were prepared using the copper(II)-catalyzed 1,3-dipolar cyclo- addition of azidobenzene 23 a or azidomethylbenzene 23 b to 4,4'-dicyanostilbene (22) at 65 8C, but the reaction did not work at this temperature probably due to steric hindrance; therefore, the temperature was increased to 120 8C. [32][33][34] The Pinner reaction was employed to obtain compounds 25 a and 25 b in yields of 22 % and 39 %, respectively, over two steps (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] The Pinner reaction was employed to obtain compounds 25 a and 25 b in yields of 22 % and 39 %, respectively, over two steps (Scheme 4). [35][36][37] For the synthesis of 4,5-disubstituted derivative 27, 4,4'-dicyanostilbene (22) was allowed to react with sodium azide at reflux in DMF to give the triazole unit in 65 % yield (Scheme 4). [48] This reaction was attempted using the copper(I)catalyzed 1,3-dipolar cycloaddition, [32][33][34] but failed possibly because the sodium azide was degraded by the catalyst (no reaction with 1.0 equiv of NaN 3 , and only 25 % product 26 formation with 2.0 equiv).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However in vivo evaluation of the present 3,5-diphenylisoxazole series has not been reported yet. [45][46][47][48][49][50][51][52][53][54][55] and also because 1,4-diphenyl-1,2,3-triazoles showed geometrical resemblance to furamidine. It was observed that the cytotoxicities of triazoles were as lower compared to that of pentamidine and were not affected by the alkylation on the amidine groups or the substitution on the aromatic rings.…”
Section: Furamidine Compoundsmentioning
confidence: 97%
“…It is especially noteworthy that 1,2,3-triazole derivatives may be considered as new entry to azole antifungal agents (Aher et al, 2009). Also, some 1,2,3-triazole derivatives were used as DNA cleaving agents (Kamal et al, 2008), potassium channel activator (Calderone et al, 2008), and cannabinoid CB1 receptor (Hou et al, 2009) and so on. 1,2,3-Triazole was stable to metabolic degradation and capable of forming hydrogen bonds, which was favoring in binding of biomolecular targets and improving solubility (Horne et al, 2004;Lv et al, 2014).…”
Section: Introductionmentioning
confidence: 99%